United States : 2008 Article IV Consultation; Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This 2008 Article IV Consultation highlights that problems in the housing and financial markets over the past year have combined to slow the United States' economy substantially. As the residential investment downturn accelerated and national indices of housing prices started falling, mortgage defaults rose sharply, and bank losses mounted. Policymakers have responded aggressively to these developments. IMF staff analysis suggests that the dollar is closer to its medium-term equilibrium level, although still on the strong side.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banks; Depository Institutions; Micro Finance Institutions; Mortgages